Cholesteryl hemiesters alter lysosome structure and function and induce proinflammatory cytokine production in macrophages - Domingues, Neuza (2017)
Rationale: Cholesteryl hemiesters are oxidation products of polyunsaturated fatty acid esters of cholesterol. Their oxo-ester precursors have been identified as important components of the "core aldehydes" of human atheromata and in oxidized lipoproteins (Ox-LDL). We had previously shown, for the first time, that a single compound of this family, cholesteryl hemisuccinate (ChS), is sufficient to cause irreversible lysosomal lipid accumulation (lipidosis), and is toxic to macrophages. These features, coupled to others such as inflammation, are typically seen in atherosclerosis. Objective: To obtain insights into the mechanism of cholesteryl hemiester-induced pathological changes in lysosome function and induction of inflammation in vitro and assess their impact in vivo. Methods and results: We have examined the effects of ChS on macrophages (murine cell lines and primary cultures) in detail. Specifically, lysosomal morphology, pH, and proteolytic capacity were examined. Exposure of macrophages to sub-toxic ChS concentrations caused enlargement of the lysosomes, changes in their luminal pH, and accumulation of cargo in them. In primary mouse bone marrow-derived macrophages (BMDM), ChS-exposure increased the secretion of IL-1 beta, TNF-alpha and IL-6. In zebrafish larvae (wild-type All and PU.1:EGFP), fed with a ChS-enriched diet we observed lipid accumulation, myeloid cell-infiltration in their vasculature and decrease in larval survival. Under the same conditions the effects of ChS were more profound than the effects of free cholesterol (FC). Conclusions: Our data strongly suggest that cholesteryl hemiesters are pro-atherogenic lipids able to mimic features of Ox-LDL both in vitro and in vivo.